2013
DOI: 10.1210/me.2012-1369
|View full text |Cite
|
Sign up to set email alerts
|

SULT2B1b Sulfotransferase: Induction by Vitamin D Receptor and Reduced Expression in Prostate Cancer

Abstract: An elevated tumor tissue androgen level, which reactivates androgen receptor in recurrent prostate cancer, arises from the intratumor synthesis of 5α-dihydrotestosterone through use of the precursor steroid dehydroepiandrosterone (DHEA) and is fueled by the steroidogenic enzymes 3β-hydroxysteroid dehydrogenase (3β-HSD1), aldoketoreductase (AKR1C3), and steroid 5-alpha reductase, type 1 (SRD5A1) present in cancer tissue. Sulfotransferase 2B1b (SULT2B1b) (in short, SULT2B) is a prostate-expressed hydroxysteroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
24
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 40 publications
5
24
1
Order By: Relevance
“…In contrast to our findings, two groups independently reported that SULT2B1b KD promotes LNCaP cell growth while maintained in androgen-depleted conditions with DHEA supplementation(19,21). Although we do not fully understand the reason(s) for this discrepancy, culture medium conditions in growth assays may play a role.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, two groups independently reported that SULT2B1b KD promotes LNCaP cell growth while maintained in androgen-depleted conditions with DHEA supplementation(19,21). Although we do not fully understand the reason(s) for this discrepancy, culture medium conditions in growth assays may play a role.…”
Section: Discussioncontrasting
confidence: 99%
“…DHEA) leading to decreased AR-dependent proliferative signaling, data herein directly show that SULT2B1b activity is positively correlated to AR activity, which implies an alternative mechanism of AR regulation is occurring. While our studies in cell lines support our previous findings that CS accumulates in precancerous and cancerous prostate tissues compared to normal counterparts, we also found that a single benign cell line, RWPE-1, has robust SULT2B1b expression and activity, which likely reflects the heterogeneity of SULT2B1b expression/activity within prostate tissue as has been reported by others(19). In contrast to the findings of Seo et al(19), recent evidence in cancer cells suggest SULT2B1b plays a role in cancer growth/aggressiveness.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To date, there are evidences linking SULT2B1b gene to tumor growth of colorectal, hepatocellular and prostate carcinoma [14][15][16]. However, the reported effects of SULT2B1b on tumor biology are conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al [14] provided the evidence that overexpression of SULT2B1b promoted cell growth and invasion in colorectal carcinoma. Yang et al [16] showed that overexpression of SULT2B1b promoted the proliferation of human hepatocarcinoma cells, whereas Seo et al [15] demonstrated that the expression of SULT2B1b was decreased in prostate cancer and depletion of SULT2B1b resulted in increased proliferation rate of prostate cancer cells. These conflicting results indicate that the role of SULT2B1b in different cancers is varies with the type of cancer.…”
Section: Discussionmentioning
confidence: 99%